Pendekatan Sosiologis Terhadap Peraturan Penanganan dan Pencegahan Kekerasan Seksual di Lingkungan Perguruan Tinggi Perspektif Feminisme Kontemporer - Abd Hannan (Realita : Jurnal Penelitian dan Kebudayaan Islam, 2022)
This article aims to examine the dynamics of sexual violence in Indonesia and the application of regulations to prevent sexual violence in universities. Methodologically, this research was conducted based on a qualitative approach. There are two types and sources of data used, primary data and secondary data. Based on the analysis of field data through the perspective of contemporary feminist theory, this study found two important findings; First, sexual crimes with motives for harassment and violence against students are currently becoming a crucial issue. This situation was triggered by weak regulatory mechanisms, unequal distribution of power, and the rootedness of a social hierarchical system that places women as a lower social group, so they tend to be treated arbitrarily. Second, efforts to deal with sexual crimes in the campus environment can be carried out through two approaches, cultural and structural. At the cultural level, there needs to be a transformation of values ​​in the cultural sector, especially in cultural systems that are biased toward patriarchal values. As for the structural level, efforts to deal with sexual crimes can be carried out by strengthening the law, both at the enforcement and protection levels. In the context of the dynamics of sexual violence on campus, a concrete form of structural effort is the implementation of Permendikbud No 30 of 2021, which contains the agenda for the Prevention and Handling of Sexual Violence (PPKS) in tertiary institutions.